1988
DOI: 10.1128/iai.56.4.910-915.1988
|View full text |Cite
|
Sign up to set email alerts
|

Combined parenteral and oral immunization results in an enhanced mucosal immunoglobulin A response to Shigella flexneri

Abstract: Achieving a vigorous secretory immunoglobulin A (IgA) response in intestinal secretions usually requires multiple doses of antigen given orally, while systemic immunity is more easily attained by parenteral immunization. This study examines the role of combined parenteral and oral immunizations to enhance the early mucosal immune response to an enteropathogen. We have used a chronically isolated intestinal-loop model in rabbits as a probe to monitor kinetically the initial (primary) local immune response to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…It has been shown in rats that as much as 90% of the serum-derived IgA is transported into the bile and that this mechanism contributes to the low level of serum IgA detected in rats (11). To enhance mucosal immunity, Keren et al (15) have reported that a parenteral dose of antigen 1 day prior to oral inoculation enhanced intestinal IgA secretion. A parenteral dose of specific antigen may be necessary to optimize the secretion of intestinal IgA prior to oral stimulation with a live-vector vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in rats that as much as 90% of the serum-derived IgA is transported into the bile and that this mechanism contributes to the low level of serum IgA detected in rats (11). To enhance mucosal immunity, Keren et al (15) have reported that a parenteral dose of antigen 1 day prior to oral inoculation enhanced intestinal IgA secretion. A parenteral dose of specific antigen may be necessary to optimize the secretion of intestinal IgA prior to oral stimulation with a live-vector vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…If so, we need to know if the sIgA response is required for protection; thus sIgA-deficient individuals should be included in the experimental groups. There is a developing literature that suggests that a combination of oral and parenteral immunization is an effective immunization strategy (120,237). This is consitent with the multiple cholera vaccine studies that suggested boosters enhance the efficacy of the current oral cholera vaccines.…”
Section: Development and Application Of An Lps-based Subunit Cholera mentioning
confidence: 99%
“…One possible approach to improve immune responses has been the use of combined mucosalp arenteral immunizations. Simultaneous parenteral^mucosal immunization [6,7], mucosal prime^parenteral boost [8,9] or parenteral prime^mucosal boost [10] strategies can generate stronger immune responses than either route alone. Induction of an immune response in speci¢c lymph nodes, for example by direct injection in or near that particular lymph node, can modulate subsequent mucosal responses developing through the same lymph node [11,12], and it has been proposed that for a parenteral prime^mucosal boost strategy to be most e¡ective, the same lymph nodes must be targeted by both routes [13].…”
Section: Introductionmentioning
confidence: 99%